Brucella abortus Strain 2308 Wisconsin Genome: Importance of the Definition of Reference Strains - Suárez-Esquivel, Marcela; Ruiz-Villalobos, Nazareth; Castillo-Zeledón, Amanda; Jiménez-Rojas, César; Roop II, R. Martin; Comerci, Diego J.; Barquero-Calvo, Elías; Chacón-Díaz, Carlos; Caswell, Clayton C.; Baker, Kate S.; Chaves-Olarte, Esteban; Thomson, Nicholas R.; et al. (Frontiers in Microbiology, 2016)
Brucellosis is a bacterial infectious disease affecting a wide range of mammals and a neglected zoonosis caused by species of the genetically homogenous genus Brucella. As in most studies on bacterial diseases, research in brucellosis is carried out by using reference strains as canonical models to understand the mechanisms underlying host pathogen interactions. We performed whole genome sequencing (WGS) analysis of the reference strain Brucella abortus 2308 routinely used in our laboratory, including manual curated annotation accessible as an editable version at www.wikipedia.Comparison of this genome with two publically available 2308 genomes showed significant differences, particularly indels related to insertional elements, suggesting variability related to the transposition of these elements within the same strain. Considering the outcome of high resolution genomic techniques in the bacteriology field, the conventional concept of strain definition needs to be revised.